MODEL INTEGRATING SOCIETY, SCIENCE, ENVIRONMENT, TECHNOLOGY AND COLLABORATIVE MIND MAPPING MEMPENGARUHI PENALARAN MATEMATIS DAN MULTIPLE INTELLEGENCES - Mujib; Mardiyah; Suherman (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
The reasoning is critical in all fields, but especially in mathematics. The purpose of this study is to ascertain the differences in students' mathematical reasoning abilities when they are exposed to learning that integrates society, science, the environment, technology, and collaborative mind mapping (ISSETCM2). This is a quasi-experiment with a population of 220 students and a sample size of 60 students. The sampling technique used is simple random sampling without replacement (without replacement). Mathematical reasoning tests based on essays and questionnaires assessing multiple intelligences. Validity, reliability, normality, homogeneity, and two-way ANOVA were used to analyze the data. The results indicated that while students' mathematical reasoning abilities improved when ISSETCM2 learning was used, there was no difference in students' mathematical reasoning abilities when conventional learning was used. Furthermore, there was no difference in students' mathematical reasoning abilities when multiple intelligences were classified as high, medium, or low. There is no interaction between learning methods and students' mathematical reasoning abilities at the high, medium, or low multiple intelligence levels.